Efficient Encryption Technique for H.264/AVC Videos Based on CABAC and Logistic Map - Fatma K Tabash; M. Izharuddin (International Journal of Informatics and Communication Technology (IJ-ICT), 2018)
Nowadays, the demands of real-time video communication are increased rapidly. Search and rescue(SAR) applications like earthquake rescue, avalanche victims, wildfire monitoring in addition to highway surveillance are considered examples of real-time applications. In which, communication time is considered the most important metric to be optimized to ensure support for victims’ lives. Thus finding a simple and time efficient encryption technique for securing the transmitted data become mandatory. In this paper, we present an efficient encryption technique which has low computation complexity, low processing time and highly chaotic encrypted videos. The proposed technique is based on CABAC where the bin-string of Intra-Prediction Mode is encrypted with chaotic signals and the sign of MVD is toggled randomly. For residue coefficients the sign of the AC coefficients are flipped randomly and the first value of DC coefficients is encrypted by XORing the bin-string with random stream. All random streams are generated with chaotic systems using Logistic map. The experimental results shows that the proposed technique is highly effective for real-time application and robust against different types of attacks.